Implementation of fuzzy logic controller for TV viewing distance detector tool - Selamet Muslimin (Yayasan Pendidikan Rafisqy Arfadhia, 2023)
This study describes the design of a safe distance detection device for watching TV using Arduino Uno. This system is expected to help reduce the risk of eye damage, especially those caused by viewing TV that is too close. This system functions to provide a warning in the form of an alarm where at a close distance the buzzer will activate and at a safe distance the buzzer will turn off. The system also provides warnings in the form of LEDs and LCDs as visual notification features, so that they can provide information to the audience to stay at a safe distance. In this study using the fuzzy logic method because this method is suitable for use in most real-time problems such as in making decisions to find variable and uncertain distances. With this fuzzy logic method, a mathematical framework is obtained that is used to represent uncertainty, ambiguity, inaccuracy, lack of information and partial truth.